Baxter elastomeric pumps: Weighing as an alternative to visual inspection. (April 2018) - Cusano, Ellen L; Ali, Raafi; Sawyer, Michael B; Chambers, Carole R; Tang, Patricia A
Purpose: Elastomeric pumps are used to administer 46-hour infusions of 5-fluorouracil (5FU). Baxter suggests patients visually monitor their pumps to ensure that infusions are proceeding correctly. This can be confusing and lead to concerns about under- or over-dosing. Baxter has not considered weighing pumps as a validated method for monitoring. This study aims to validate weighing as a more accurate method for patients and healthcare professionals, and describe real life Baxter Infusor™ variability. Methods: Patients who had been started on a 46-hour 5FU infusion returned to the clinic approximately 24 h after starting treatment. The pump was weighed on a StarFrit kitchen scale, and date, time, and weights recorded. Patients were asked if they had a preference for weighing or visually inspecting their pump. Results: Pumps ( n  = 103) were weighed between 17.25 and 27.5 h after connection. The average weight of a pump was 189 g. Of 103 pumps weighed, 99 weighed less than expected, corresponding to average flow rates of 5.69 mL/h over the elapsed time. The expected flow rate is 5 mL/h with 10% variability. Average flow rates within the 17.25- to 27.5-hour window were 4.561 mL/h, which is 8.78% slower than expected, but within the 10% known variability. Forty-seven percent of patients didn't have a preference for either method, but for those who did have a preference, more than twice as many preferred weighing. Conclusion: With proper education, weighing Baxter Infusors at home with kitchen scales can be an accepted and objective alternative to the current recommendation of visual inspection.